Narrative Development in Young Children : Gesture, Imagery, and Cohesion - Levy, Elena T.; McNeill, David (Cambridge : Cambridge University Press, 2015)
As children begin to use language in early childhood, they produce increasingly large units of coherent speech, including narrative descriptions of events. This book examines the process of narrative development in young children, focusing on the development of'cohesion' - the use of speech and gesture to create coherent perspectives on events. Surveying early narrative development in which gesture plays an integral part, the book explores the development of cohesive, clause-linking devices during the period from age two to three. Illustrated with longitudinal cases studies, the book examines the crib-talk of two-year-old Emily and compares it to the discourse patterns of storybooks and nursery rhymes, and to her father's pre-bedtime routines. In a second case study, the authors trace the changing relationships between speech and gesture in the spontaneous narratives of two-year-old Ella. This book will be invaluable to students and researchers in language acquisition, developmental psychology and gesture studies.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Communicative competence in children; Language acquisition; Gesture